Rome and Persia at War : Imperial Competition and Contact, 193-363 CE - Edwell, Peter (Taylor & Francis Group, 2020)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Acknowledgements -- 1 Introduction -- 2 Rome and Parthia: Conflict and Diplomacy from Sulla to Caracalla -- 3 Conflict and Diplomacy between Rome and Persia from Ardashir to Philip I -- 4 Persian Triumph, Roman Defeat -- 5 The last Years of the Reign of Shapur I to the Persian Invasion of Carus -- 6 The Relationship between Rome and Persia During the Reigns of Diocletian, Bahram II and Narseh -- 7 Rome and Persia during the Reigns of Constantine and Shapur II -- 8 Conflict and Diplomacy between Rome and Persia under Constantius II and Shapur II -- 9 The Persian Invasion of the Emperor Julian and its aftermath -- 10 Conclusion -- Bibliography -- Index.